valuación de la expresión del gen GLP-1 (péptido 1 homologo al glucagón) en ratas inducidas a Diabetes Mellitus tipo 2 tratadas con extracto metanólico de Schkuhria pinnata (Canchalagua) - Zúñiga Gutierrez y Cols., María Alejandra (2019)
The expression of GLP-1 gene was evaluated in rats induced to type 2 Diabetes Mellitus and treated with methanol extract of Schkuhria pinnata (Canchalagua). In vivo studies were performed. Experimental type 2 diabetes was induced in 4 months age Wistar novergicus male rats by administration of StreptozotocinNicotinamide (65mg/kg and 330mg/kg), then, diabetes was confirmed by monitoring the glucose variation and histopathology of diabetic´s pancreas. The hypoglycemic effect of Schkuhria pinnata (Canchalagua) was evaluated during 25 days after the induction of experimental diabetes, showing a statistically significant decrease (P <0.05) in groups C, D and E (rats induced to type 2 diabetes experimental treated with Metformin 330mg/kg, methanolic extract of Canchalagua a 20 mg/kg y 40 mg/kg, respectively) since day 10, reaching normal values of glycemia at the end of the experiment. Subsequently, the GLP-1 gene expressions were evaluated in the rat distal small intestines by qPCR and the results showed that the group B expression was down-regulated by the factor 41.319 in comparison with the group A (normal rats), the group C, showed an upregulation with the factor 16.694 compared with group A, and the experimental groups D and E showed expressions up-regulated by the factors 7.292 and 7.761 in comparison with the group A.